PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 28 PADANG - Rahayu, Anggun; Basri, Irfani; Abdurahman, Abdurahman (Universitas Negeri Padang, 2016)
ABSTRACT This article was to describe the effects of the using of discovery learning model using audiovisual media toward student of writing news skill at grade VIII SMP Negeri 28 Padang. The method used was experiment method. Based on data analysis it could be concluded three points as follow. First, student’s writing a news skill at grade VIII SMP Negeri 28 Padang was moderate with mean score 73,53 without using of model discovery learning aided audiovisual media. Second, students’s writing news skill at grade VIII SMP Negeri 28 Padang using of model discovery learning aided audiovisual media was good with mean score 79,68. Third, based on t-test it could be conclude that there was the effects of model discovery learning using audiovisual media toward student’s writing news skill at grade VIII SMP Negeri 28 Padang because taritmatic> t table (3,04>1,67). Kata kunci: pengaruh, model discovery learning, media audiovisual, menulis berita